Colour Metallography of Cast Iron - Chapter 2: Grey Iron (Ⅲ) - Zhou Jiyang (China Foundry, 2009)
The book, Colour Metallography of Cast Iron , uses colour metallography technique to study solidification structures of cast irons: graphite, carbides, austenite and eutectics; and focuses on solidification processes. With progress of modern solidification theory, the control of material solidification process becomes important measure for improving traditional materials and developing new materials. Solidification structure not only influences mechanical and physical properties of cast iron, but also affects its internal quality. The book uses a large amount of colour photos to describe the formation of solidification structures and their relations. Crystallization phenomena, which cannot be displayed with traditional metallography, are presented and more phase transformation information is obtained from these colour metallographic photos. This book consists of five sections: Chapter 1 Introduction, Chapter 2 Grey Iron, Chapter 3 Ductile Iron, Chapter 4 Vermicular Cast Iron, and Chapter 5 White Cast Iron. CHINA FOUNDRY publishs this book in several parts serially,starting from the first issue of 2009.